2018
DOI: 10.1371/journal.pone.0191141
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of cone density, spacing and arrangement in adult healthy retinas with adaptive optics flood illumination

Abstract: The aim of this article is to analyse cone density, spacing and arrangement using an adaptive optics flood illumination retina camera (rtx1™) on a healthy population. Cone density, cone spacing and packing arrangements were measured on the right retinas of 109 subjects at 2°, 3°, 4°, 5° and 6° of eccentricity along 4 meridians. The effects of eccentricity, meridian, axial length, spherical equivalent, gender and age were evaluated. Cone density decreased on average from 28 884 ± 3 692 cones/mm2, at 2° of eccen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
68
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(93 citation statements)
references
References 36 publications
(78 reference statements)
23
68
2
Order By: Relevance
“…[40][41][42] The counted cone densities at IS/OS and COST at 2.58 and 6.58 ecc were in agreement with AO-FC/SLO examinations of healthy eyes although these modalities are incapable of separating IS/OS from COST signals and show a mixture of signals from all outer retinal layers. [43][44][45] The oscillation of IS/ OS and COST signals, which were especially visible in our IS/ OS þ COST false-color composite images, were also found with other AO-OCT systems and are most likely a sign of PR segment renewal. 38,39,46 Apart from morphologic factors, technical aspects, such as the wavelength or the type of light source, could contribute to this variation in reflectance properties.…”
Section: Discussionsupporting
confidence: 69%
“…[40][41][42] The counted cone densities at IS/OS and COST at 2.58 and 6.58 ecc were in agreement with AO-FC/SLO examinations of healthy eyes although these modalities are incapable of separating IS/OS from COST signals and show a mixture of signals from all outer retinal layers. [43][44][45] The oscillation of IS/ OS and COST signals, which were especially visible in our IS/ OS þ COST false-color composite images, were also found with other AO-OCT systems and are most likely a sign of PR segment renewal. 38,39,46 Apart from morphologic factors, technical aspects, such as the wavelength or the type of light source, could contribute to this variation in reflectance properties.…”
Section: Discussionsupporting
confidence: 69%
“…Adaptive optics retinal imaging studies have shown that, in and around the fovea, axial elongation of the eye in myopia is generally such that the angular spacing between adjacent cone photoreceptors remains constant (i.e., physical density is reduced, consistent with a geometric ''stretch'' of the globe). [31][32][33] Psychophysical measurements of resolution acuity and spatial summation in myopic eyes are consistent with a reduction in retinal ganglion cell density, over and above that implied from such a ''simple'' physical stretch. 34,35 The results of the present study indicate that, in angular units, the geometry of retinal nerve fiber bundles was not differentiable between highly myopic and nonmyopic eyes.…”
Section: Trajectory Of Temporal Retinal Nerve Fiber Bundlesmentioning
confidence: 64%
“…Mean subject age was 25 years (range, [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] and spherical equivalent (SE) ranged from 0D to À13D (minimum 10 subjects per 1D range of refraction between 0D to À5D; 27 subjects in the range À3 to À6D; 17 subjects beyond À6D). Axial length and vitreous chamber depth (VCD) were measured by A-scan ultrasonography (AL-100 biometer; Tomey GmbH, Nürnberg, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…It is known that the hyperautofluorescent ring manifests as an ellipsoid in the early stages of RP [10], which would imply that there are differences in the lengths of the vertical and horizontal diameters when the disease first becomes evident with SW-AF. Studies using adaptive optics flood illumination have revealed histological and anatomical differences in the photoreceptor distribution between both vertical and horizontal meridians, which may explain the ellipsoid shape of the ring [24,25]. Nevertheless, this ellipsoid has been observed to progressively evolve into a uniformly round shape, which occurs due to a difference in the rate of one ring diameter's constriction compared to that of the other diameter.…”
Section: Discussionmentioning
confidence: 99%